Outcomes for Treatment of Hypersexual Behavior Provided by Specialized Social Welfare Units. (January 2019) - Kjellgren, Cecilia
Purpose: This study explores outcomes of treatment provided by specialized units within the social welfare sector in Sweden to clients seeking help with hypersexual behavior. Method: The participants were 27 males and 1 female ( M = 40.3 years) who sought help from one of the three specialized units within social welfare in Sweden. A pretest–posttest group design was used to assess changes after treatment. Quantitative data were collected through interviews and self-report forms. Results: At posttreatment stage (on average a 10-month follow-up), mental health was significantly improved and hypersexual behavior reportedly reduced. The treatment at the specialized units appeared to help the clients. Conclusions: The specialized units seemed to deliver favorable service without shaming and stigmatizing participants. As this study can be considered a pilot study, it needs to be replicated.